Time-resolved co-transport dynamics of microplastics and antibiotic resistance genes during stormwater first flush - Taehwan Lee; Hongmok Jo; Min-Sang Kim; Yeongmi Park; Uijeong Han; Jaehun Gwon; Seon-Young Kim; Seunghyun Lee; Ran Kim; Hyoyoung Lee; Gopalakrishnan Kumar; Si-Kyung Cho (Environmental Research, 2026)

Multicolor vanadium dioxide-polyvinylpyrrolidone/silver bilayer smart films for reconfigurable visible color and solar energy modulation - Yoonjoo Choi; Byoungsu Ko; Hyungyoon Choi; Giyong Park; Sunga Kim; Ho Young Woo; Da Won Lee; Ran An; Yerin Kim; Sung-Hoon Hong; Junsuk Rho; Tianshuo Zhao; et al. (Chemical Engineering Journal, 2026)

A Novel Strain Bifidobacterium longum subsp. longum HN001 Ameliorates High-Fat Diet-Induced Obesity in Mice Through Microbiome-Associated Short-Chain Fatty Acids - Chae Hwan Lee; Youngji Han; Joo Young Ryu; Minseo Jung; Chae Rin Park; Mi Ran Jang; Youn Gil Kwak; Hanvit Cha; Jin Hyup Lee (Probiotics and Antimicrobial Proteins, 2026)

Integrated hydroprocessing and microbial biotransformation of coconut oil to α,ω-diacids - Bashu Dev Pardhe; Il-Ho Choi; Chang Hoon Lee; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Hwabong Jeong; Jongbeom Park; Kyung Taek Heo; et al. (Bioresource Technology, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

Eco-friendly biocontrol of pine wilt disease: Enhancing tree defense with Bacillus subtilis JCK-1398 for sustainable forest management - Mohamed Mannaa; Ae ran Park; Jungwook Park; Hee Won Jeon; Hyejung Jung; Hyo Seong Jeon; Gil Han; Jin-Cheol Kim; Young-Su Seo (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Accelerating ionic–electronic percolation pathways via catecholate coordination of bioinspired-polymer dopamine in all-solid-state composite cathode - Thuy Hoai Linh Vuong; Naila Riaz Mastoi; Jae Seok Nam; Weerawat To A Ran; Cheayeon Ha; Min-Sik Park; Young-Jun Kim (Chemical Engineering Journal, 2024)

Safety of applying influenza-antigen-coated microneedles to rat skin and the antigen specific immune response in vivo - Taek-Seon Yun; Bomin Song; Yu-Rim Hwang; Minki Jin; Hyeseung Seonwoo; Donki Kim; Hye Won Kim; Byeong Cheol Kim; Daekyung Kim; Boyeong Park; Jeong Yeon Kang; Seung-Ki Baek; et al. (Journal of Pharmaceutical Investigation, 2024)

Molecular mapping of the broad bean wilt virus 2 resistance locus bwvr in Capsicum annuum using BSR-seq - Jung-Min Kim; Joung-Ho Lee; Se-Ran Park; Jin-Kyoung Kwon; Na-Young Ro; Byoung-Cheorl Kang (Theoretical and Applied Genetics, 2024)
Key message Bulked segregant RNA seq of pools of pepper accessions that are susceptible or resistant to Broad bean wilt virus 2 identifies a gene that might confer resistance to this devastating pathogen. Abstract The single-stranded positive-sense RNA virus Broad bean wilt virus 2 (BBWV2) causes substantial damage to pepper ( Capsicum annuum ) cultivation. Here, we describe mapping the BBWV2 resistance locus bwvr using a F 7:8 recombinant inbred line (RIL) population constructed by crossing the BBWV2-resistant pepper accession ‘SNU-C’ with the susceptible pepper accession ‘ECW30R.’ All F 1 plants infected with the BBWV2 strain PAP1 were susceptible to the virus, and the RIL population showed a 1:1 ratio of resistance to susceptibility, indicating that this trait is controlled by a single recessive gene. To map bwvr , we performed bulked segregant RNA-seq (BSR-seq). We sequenced pools of resistant and susceptible lines from the RILs and aligned the reads to the high-quality ‘Dempsey’ reference genome to identify variants between the pools. This analysis identified 519,887 variants and selected the region from 245.9–250.8 Mb of the Dempsey reference genome as the quantitative trait locus region for bwvr . To finely map bwvr , we used newly designed high-resolution melting (HRM) and Kompetitive allele specific PCR (KASP) markers based on variants obtained from the BSR-seq reads and the PepperSNP16K array. Comparative analysis identified 11 SNU-C-specific SNPs within the bwvr locus. Using markers derived from these variants, we mapped the candidate bwvr locus to the region from 246.833–246.949 kb. SNU-C-specific variants clustered near DEM.v1.00035533 within the bwvr locus. DEM.v1.00035533 encodes the nitrate transporter NPF1.2 and contains a SNP within its 5′ untranslated region. The bwvr locus, which contains four genes including DEM.v1.00035533, could represent a valuable resource for global pepper breeding programs.

Diuron-induced fetal Leydig cell dysfunction in in vitro organ cultured fetal testes - Ran Lee; Won-Young Lee; Hyun-Jung Park (Reproductive Toxicology, 2024)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Nanoscale level gelatin-based scaffolds enhance colony formation of porcine testicular germ cells - Ran Lee; Hyun Jung Park; Won Young Lee; Youngsok Choi; Hyuk Song (Theriogenology, 2023)

Correction to: A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2022)

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2021)

The chemical constituents of ethanolic extract from Stauntonia hexaphylla leaves and their anti-inflammatory effects - Le Ba Vinh; Se Jin Jo; Phong Nguyen Viet; Dan Gao; Kyoung Won Cho; Eun-Jeong Koh; Sung Sun Park; Young Ran Kim; Young Ho Kim; Seo Young Yang (Natural Product Research, 2021)

Risk factors for development and mortality of invasive pulmonary Aspergillosis in kidney transplantation recipients - Hyeri Seok; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Woo Seong Huh; Jae Berm Park; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Particle number size distributions generated by different Korean pork cooking methods - Soo Ran Won; In-Keun Shim; Myunghee Kwon; Hyun Ah Ji; Ki-soo Park; Young Sung Ghim (Air Quality, Atmosphere & Health, 2020)

Clinical factors influencing the performance of bacterial multiplex polymerase chain reaction in patients with community-onset pneumonia - Ga Eun Park; Kyong Ran Peck; Jae-Hoon Ko; Cheol-In Kang; Sun Young Cho; Doo Ryeon Chung; Nam Yong Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Arabidopsis zinc finger homeodomain protein ZHD5 promotes shoot regeneration and confers other cytokinin-related phenotypes when overexpressed - Jin-Baek Kim; Jung-Youn Kang; Min Young Park; Mi-ran Song; Young Cheol Kim; Soo Young Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Metformin Inhibits the Development of l-DOPA-Induced Dyskinesia in a Murine Model of Parkinson’s Disease - Young-Kyoung Ryu; Hye-Yeon Park; Jun Go; Dong-Hee Choi; Yong-Hoon Kim; Jung Hwan Hwang; Jung-Ran Noh; Tae Geol Lee; Chul-Ho Lee; Kyoung-Shim Kim (Molecular Neurobiology, 2018)

6-Hydroxydopamine induces nuclear translocation of apoptosis inducing factor in nigral dopaminergic neurons in rat - Hong-Il Yoo; Gil-Yeong Ahn; Eun-Jin Lee; Eu-gene Kim; Sung-Young Hong; Sang-Jin Park; Ran-Sook Woo; Tai-Kyoung Baik; Dae-Yong Song (Molecular & Cellular Toxicology, 2017)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Neuroanatomical distribution of galectin-3 in the adult rat brain - Hong-Il Yoo; Eu-Gene Kim; Eun-Jin Lee; Sung-Young Hong; Chi-Sun Yoon; Min-Ju Hong; Sang-Jin Park; Ran-Sook Woo; Tai-Kyoung Baik; Dae-Yong Song (Journal of Molecular Histology, 2017)

Alternative new mesenchymal stem cell source exerts tumor tropism through ALCAM and N-cadherin via regulation of microRNA-192 and -218 - Ran Kim; Sang In Park; Chang Youn Lee; Jihyun Lee; Pilseog Kim; Sekyung Oh; Hojin Lee; Min Young Lee; Jongmin Kim; Yong-An Chung; Ki-Chul Hwang; Lee-So Maeng; et al. (Molecular and Cellular Biochemistry, 2017)

Fermented Saccharina japonica (Phaeophyta) improves neuritogenic activity and TMT-induced cognitive deficits in rats - Hyun-Jung Park; Mi-Sook Lee; Hyun Soo Shim; Gyeong-Ran Lee; Sun Yong Chung; Young Mi Kang; Bae-Jin Lee; Yong Bae Seo; Kyung Soo Kim; Insop Shim (Algae, 2016)

Endosulfan induces COX-2 expression via NADPH oxidase and the ROS, MAPK, and Akt pathways - Hyung Gyun Kim; Young Ran Kim; Jin Hee Park; Tilak Khanal; Jae Ho Choi; Minh Truong Do; Sun Woo Jin; Eun Hee Han; Young Ho Chung; Hye Gwang Jeong (Archives of Toxicology, 2015)

Memory Impairment in Estrogen Receptor α Knockout Mice Through Accumulation of Amyloid-β Peptides - Chul Ju Hwang; Hyung-Mun Yun; Kyung-Ran Park; Ju Kyung Song; Hyun Ok Seo; Byung Kook Hyun; Dong Young Choi; Hwan-Soo Yoo; Ki-Wan Oh; Dae Yeun Hwang; Sang-Bae Han; Jin Tae Hong (Molecular Neurobiology, 2015)

Transcriptomic study of mouse embryonic neural stem cell differentiation under ethanol treatment - Chanchal Mandal; Ji Hyun Park; Mi Ran Choi; Sun Hwa Kim; Abimbola Comfort Badejo; Jin Choul Chai; Young Seek Lee; Kyoung Hwa Jung; Young Gyu Chai (Molecular Biology Reports, 2015)

Mercury contamination and exposure assessment of fishery products in Korea - Hye-Ran Yang; Na-Young Kim; Lae-Hong Hwang; Ju-Sung Park; Jung-Hun Kim (Food Additives & Contaminants Part B-Surveillance, 2015)

Polymorphisms of interleukin-31 are associated with anti-CCP levels in females with rheumatoid arthritis - JI-IN YU; YOUNG-RAN PARK; SHIN-SEOK LEE; SOO-CHEON CHAE (Journal of Genetics, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

Transcriptional changes of gibberellin oxidase genes in grapevines with or without gibberellin application during inflorescence development - Chan Jin Jung; Youn Young Hur; Sung-Min Jung; Jung-Ho Noh; Gyung-Ran Do; Seo-June Park; Jong-Chul Nam; Kyo-Sun Park; Hae-Sung Hwang; Doil Choi; Hee Jae Lee (Journal of Plant Research, 2014)

Synechocystis PCC6803 and PCC6906 dnaK2 expression confers salt and oxidative stress tolerance in Arabidopsis via reduction of hydrogen peroxide accumulation - Jonghyun Kim; Myung Suk Ahn; Young Min Park; Suk Weon Kim; Sung Ran Min; Weon Joong Jeong; Jang R. Liu (Molecular Biology Reports, 2014)

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal inhibits tumor growth via suppression of NF-κB and induction of death receptor 6 - Jung Ok Ban; Young-Suk Jung; Dae Hwan Kim; Kyung-Ran Park; Hyung-Mun Yun; Nam Jin Lee; Hee Pom Lee; Jeong-Hyun Shim; Heon-Sang Jeong; Yun-Hee Lee; Young Wan Ham; Sang-Bae Han; et al. (Apoptosis, 2014)

SPARC is involved in the maintenance of mitotically inactivated mouse embryonic fibroblast cells - Jun Yeon Won; Young Jin Lee; Seung-Joon Lee; Woo Jin Kim; Seon-Sook Han; Se-Ran Yang; Heung-Myong Woo; Sung-Min Park; Hyang-Ah Lee; Seok-Ho Hong (In Vitro Cellular & Developmental Biology - Animal, 2013)

Molecular characterization of KGH, the first human isolate of rabies virus in Korea - Jun-Sun Park; Chi-Kyeong Kim; Su Yeon Kim; Young Ran Ju (Virus Genes, 2013)

Analysis of Substrate Recognition Site 2 (SRS2) in human cytochrome P450 1A2 using whole-plasmid random mutagenesis - Joohwan Kim; Songhee Han; Seunghye Choi; Hyoung-Goo Park; Young-Ran Lim; Hwayoun Lee; Donghak Kim (Molecular & Cellular Toxicology, 2013)

Functional Analysis of Histone Demethylase Jmjd2b on Lipopolysaccharide-Treated Murine Neural Stem Cells (NSCs) - Nando Dulal Das; Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Hyung Tae Lee; Amitabh Das; Seung Hyun Kim; Young Gyu Chai (Neurotoxicity Research, 2013)

Phylogenetic analysis of porcine astrovirus in domestic pigs and wild boars in South Korea - Meong-Hun Lee; Hye-Young Jeoung; Hye-Ran Park; Ji-Ae Lim; Jae-Young Song; Dong-Jun An (Virus Genes, 2013)

Comparative analysis of pathogenesis-related protein 10 (PR10) genes between fungal resistant and susceptible peppers - Hyun Cheol Soh; Ae Ran Park; Sangkyu Park; Kyoungwhan Back; Jae Bok Yoon; Hyo Guen Park; Young Soon Kim (European Journal of Plant Pathology, 2012)

Temporal changes in the abundance of the fish-killing dinoflagellate Karlodinium veneficum (Dinophyceae) in Tongyeong, Korea - Tae-Gyu Park; Yu-Ran Ok; Young-Tae Park; Chang-Kyu Lee (Algae, 2011)

Real-time detection of cellular apoptosis using a rat C6 glioma cell-based assay system - Kyoung Hwa Jung; Young Me Song; Nando Dulal Das; Kyoung Sun Park; Mi Ran Choi; Sang Youn Hwang; Eun Kyu Lee; Moon Kwon Lee; Jaebum Choo; Kyoung Suk Kim; Moo Soung Kim; Sang Rin Lee; et al. (Molecular & Cellular Toxicology, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Ethanol-induced small heat shock protein genes in the differentiation of mouse embryonic neural stem cells - Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Nando Dulal Das; Mi Kyung Chung; Ihn Geun Choi; Boung Chul Lee; Kyoung Sun Park; Young Gyu Chai (Archives of Toxicology, 2011)

Bile tolerant Lactobacillus reuteri isolated from pig feces inhibits enteric bacterial pathogens and porcine rotavirus - Byeong Joo Seo; Mi Ran Mun; Rejish Kumar V. J; Chul-Joong Kim; Insun Lee; Young-Hyo Chang; Yong-Ha Park (Veterinary Research Communications, 2010)

Characterization of a mannose-6-phosphate isomerase from Geobacillus thermodenitrificans that converts monosaccharides - Soo-Jin Yeom; Nam-Hee Kim; Ran-Young Yoon; Hyun-Jung Kwon; Chang-Su Park; Deok-Kun Oh (Biotechnology Letters, 2009)

In vitro and in planta Interaction Evidence between Nicotiana tabacum Thaumatin-Like Protein 1 (TLP1) and Cucumber mosaic virus Proteins - Min Jung Kim; Byung-Kook Ham; Hwa Ran Kim; In-Ju Lee; Young Jin Kim; Ki Hyun Ryu; Young In Park; Kyung-Hee Paek (Plant Molecular Biology, 2005)

The suggestive association of eotaxin-2 and eotaxin-3 gene polymorphisms in Korean population with allergic rhinitis - Soo-Cheon Chae; Young-Ran Park; Gyung-Jae Oh; Jae-Hoon Lee; Hun-Taeg Chung (Immunogenetics, 2005)

The polymorphisms of Tim-1 promoter region are associated with rheumatoid arthritis in a Korean population - Soo-Cheon Chae; Young-Ran Park; Ju-Hee Song; Seung-Cheol Shim; Kyung-Sik Yoon; Hun-Taeg Chung (Immunogenetics, 2005)

Anti-fungal effects of phenolic amides isolated from the root bark of Lycium chinense - Dong Gun Lee; Yoonkyung Park; Mi-Ran Kim; Hyun Jun Jung; Young Bae Seu; Kyung-Soo Hahm; Eun-Rhan Woo (Biotechnology Letters, 2004)

Expression of Interferon Inducible Genes Following Hantaan Virus Infection as a Mechanism of Resistance in A549 Cells - Jae-Hwan Nam; Kyung-A Hwang; Cheong-Hee Yu; Tae-Hoon Kang; Jae-Young Shin; Woo-Young Choi; In-Beom Kim; Young-Ran Joo; Hae-Wol Cho; Keun-Yong Park (Virus Genes, 2003)